Comparison of Patterns of Lipid Profile in Type-2 Diabetics and Non- Diabetics - FIRDOUS, S; KHAN, M Z (Annals of King Edward Medical University, 2021)
Objective: To determine the commonest pattern of lipid profile in type 2 diabetics presenting in Mayo hospital and to compare it with non-diabetics. Study design: It was a comparative study. Place: It was conducted in all medical wards, medical OPD and patients seen in emergency. Material and method: Patients were selected according to inclusion criteria. After sampling for all relevant investigations, results were expressed after applying Chi-square test. Results: Serum cholesterol> 240mg/dl seen in 25% diabetics and 11 % non-diabetics (p <0.05). Levels <240 and >200mg/dl seen in 35% diabetics and 19% non-diabetics (p <0.05).Serum cholesterol < 200rng/dl seen in 40% diabetics and 70% non-diabetics (p<0.05).LDL >160mg/dl seen in 21% diabetics and 5% non-diabetics (p<0.01).LDL <130mg/dl seen in 32% diabetics and 42% non-diabetics (p >0.05).HDL < 35 mg/dl seen in 67% diabetics and 43% non-diabetics (p <0.05). HDL >35rng/ dl seen in 33% diabetics and 57% non-diabetics (p<0.05). TG >400 mg/dl seen in 8% diabetics and 3% non-diabetics, TG >200rng/dl seen in 38% diabetics and 93% non-diabetics (p<0.01).TG <200mg/dl seen in 62% diabetics and 3% diabetics (p<0.01). Conclusion: Diabetes and cardiovascular disease are closely associated. Diabetic dyslipidaernias are a major risk factor for athrosclerosis. The commonest dyslipidaemia found was low HDL cholesterol followed by high LDL ,serum cholesterol and TG levels. The commonest dyslipidaemia found among non-diabetics in this study is high TG and low HDL, which might be associated with dietary factors and lack of exercise. Correction of dyslipidaemia is important to retard the progression of atherosclerosis.